The Bio-Efficacy of Crude Leaf Extract (Murraya Koenigii) as Botanical Termiticides Against Subterranean Termite, Coptotermes Gestroi - Munirah Muda, Siti; Salihah Kamarozaman, Aisyah; Mohamad, Azlinda; Ariff Nafizi Ibrahim, Mohd; Mohd Zani, Amirudin; Muhammud, Adida (International Journal of Engineering and Technology, 2018)
Termites are widely considered as destructive polyphagous insect pests that give problematic issues to the environment and health since chemical and synthetic termiticides are used persistently to control these insect pests. This has caused a great hazard to the environment due to the chemical residual effects. Therefore, the aim of this paper is to explore the toxicity of Murraya Koenigii crude leaf extract against subterranean termites. They are the typical species of termites that are responsible for the cause of damage to the manmade structures in Malaysia. In this study, a toxicity determination was conducted through five different concentrations of the Murraya Koenigii extract; with various measurement of 0.5, 1, 2.5, 5, and 10 mg/ml; to the termite species under laboratory conditions. From the observation, the crude leaf extract displays a significant anti termiticidal activity after two weeks of exposures to the post treatment. The termites responded differently to the filter papers that were treated with varying concentration of extracts beforehand. Consequently, the frequent exposures to the high concentration of the crude leaf extract will increase the mortality rates of the termites. Instead, the control group disclosed less than 5% of the mortality rates. Thus, the experiment shows that Murraya Koenigii crude leaf extraction exhibits significant insecticidal property against the termites since it contains a bioactive compound known as linalool that is responsible for termite control and termiticidal activity.Â